2005
DOI: 10.1159/000086952
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Aggrus (T1alpha/Podoplanin), a Platelet-Aggregation-Inducing Factor in Lung Squamous Cell Carcinoma

Abstract: Aggrus (T1α/podoplanin, known as a specific marker for type I alveolar cells or lymphatic endothelial cells) is a transmembrane sialoglycoprotein that aggregates platelets. Previously, we showed that upregulated expression of Aggrus occurs in colorectal tumors or testicular tumors and could be associated with platelet-aggregating activity and metastatic ability. In testicular tumors, Aggrus is specifically expressed in seminoma. The present study investigates Aggrus expression in human primary lung cancer tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 200 publications
(139 citation statements)
references
References 16 publications
7
127
0
5
Order By: Relevance
“…23 In vitro studies suggested that podoplanin may be involved in mediating cell motility and adhesion. 23,24 Very recently, podoplanin expression was reported in squamous cell carcinomas of the epidermis, 13 oral cavity, 24 and lung, 25 and it was suggested that it may be involved in tumor cell invasion, metastasis, and tumor progression. In addition, mucin-type glycoproteins, such as podoplanin, are expressed widely on human normal cells and tumors [26][27][28] and have recently been implicated in cellular signaling, cell adhesion, tumor growth, and suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…23 In vitro studies suggested that podoplanin may be involved in mediating cell motility and adhesion. 23,24 Very recently, podoplanin expression was reported in squamous cell carcinomas of the epidermis, 13 oral cavity, 24 and lung, 25 and it was suggested that it may be involved in tumor cell invasion, metastasis, and tumor progression. In addition, mucin-type glycoproteins, such as podoplanin, are expressed widely on human normal cells and tumors [26][27][28] and have recently been implicated in cellular signaling, cell adhesion, tumor growth, and suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of podoplanin is upregulated in a number of different human cancers, including squamous cell carcinoma of the oral cavity, the larynx, the lung, the cervix, the oesophagus, and the skin, in dysgerminomas of the ovary and granulosa cell tumours, in mesothelioma, and in many tumours of the central nervous system (CNS) (Kato et al, 2005;Kimura and Kimura, 2005;Martin-Villar et al, 2005;Schacht et al, 2005;Shibahara et al, 2006;Wicki et al, 2006). The oncofetal M2A antigen expressed in testicular germ cell tumours is identical to podoplanin (Dumoff et al, 2005).…”
Section: Podoplanin Is Upregulated In the Outer Edge Of The Tumour Massmentioning
confidence: 99%
“…Podoplanin expression is upregulated in different types of experimental and human tumors, including squamous cell carcinomas of the skin, lung, esophagus, cervix, larynx and oral cavity (Gandarillas et al, 1997;Martín-Villar et al, 2005;Schacht et al, 2005;Kato et al, 2005;Wicki et al, 2006), colorectal adenocarcinomas , testicular germ cell tumors (Kato et al, 2004;Schacht et al, 2005) and mesotheliomas (Chu et al, 2005). In squamous cell carcinomas, podoplanin expression is frequently restricted to the invasive front (Martín-Villar et al, 2005;Wicki et al, 2006), and in some tumors correlates with downregulation of the cell-cell adhesion protein E-cadherin (Martín-Villar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%